10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Meniscus root repair has been shown to improve symptoms and protect against progressive knee arthritis by restoring more normal weightbearing force distribution. While advanced tibiofemoral chondrosis is known to negatively affect root repair outcomes, there is a paucity of literature describing the impact of concomitant patellofemoral chondrosis (PFC). PURPOSE: To evaluate outcomes of meniscus root repair in patients with and without advanced PFC. STUDY DESIGN: Cohort study; Level of evidence, 3. METHODS: This single-center retrospective study included patients who underwent isolated posterior medial meniscus root repair (PMMRR) between July 2013 and February 2023, with a minimum 2-year follow-up. Based on intraoperative arthroscopic findings, patients were stratified into 2 groups: those with PFC, defined as Outerbridge grade ≥3, and those without PFC (Outerbridge grade < 3). Clinical outcomes, including meniscal retear, conversion to unicompartmental knee arthroplasty (UKA) or total knee arthroplasty (TKA), and revision meniscal surgery, were obtained through chart review. Patient-reported outcomes (PROs) were collected from patients without retear or revision meniscal surgery and who did not convert to UKA or TKA and included the Knee injury and Osteoarthritis Outcome Score-12 (KOOS-12), International Knee Documentation Committee (IKDC) subjective score, and return-to-sport status. RESULTS: A total of 115 patients were included: 67 with PFC (mean age, 55.0 years; 82.1% female) and 48 non-PFC controls (mean age, 52.0 years; 66.7% female). The mean follow-up duration was 6.2 years for the PFC group and 5.7 years for the non-PFC group. At the final follow-up, there were no significant differences between groups in KOOS-12 Pain, Function in Daily Living, or Quality of Life subscales; IKDC scores; or return-to-sport rates (all P > .05). Rates of Patient Acceptable Symptom State, minimal clinically significant difference, and substantial clinical benefit achievement were also similar. Retear rates (11.9% for PFC and 8.3% for non-PFC) and revision meniscal surgery rates (1.5% for PFC and 4.2% for non-PFC) were similar between groups. However, the PFC group demonstrated a significantly higher rate of conversion to UKA or TKA compared with the non-PFC group (14.9% vs 2.1%; P = .021). CONCLUSION: Patients with and without PFC at the time of PMMRR who did not experience a retear, undergo revision surgery, or convert to UKA or TKA had comparable PROs and clinically significant outcomes at the final follow-up. However, there was a significantly higher rate (almost 7-fold) of conversion to UKA or TKA in patients with PFC, suggesting that while short- to midterm functional outcomes may be preserved, advanced PFC may predispose patients to earlier progression of joint degeneration and need for arthroplasty.